2018
DOI: 10.1021/acs.jpca.8b05015
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Simulations of the Acidity Dependence of the Kinetics of the Iron-Catalyzed Belousov–Zhabotinsky Reaction: Proton-Catalysis in the Electron Transfer Reaction Involving the [Fe(phen)3]3+ Species

Abstract: The acidity dependence of the iron-catalyzed bromate-malonic acid Belousov-Zhabotinsky reaction was studied in the range 0.36 M < [HSO] < 1.20 M, and the temporal evolutions of the oscillation patterns were analyzed. The experimental results show that the period times PT decrease exponentially with increasing acidity and that the period times parallel the decrease of the reduction times RT with increasing acidity. Simulations using the reactions of the commonly accepted core reaction mechanism failed to match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…20 higher oxidization state catalyst (R8 in FKN mechanism). 21 In varying the sulfuric acid concentration in the iron-catalyzed BZR, we found a strong inverse dependence of period time on acidity. In simulations of the kinetics of the iron-catalyzed reaction, strong agreement with experiment was found by including second-order proton catalysis of the electron transfer reaction (reaction R9 in ref 21, shown below) between [Fe(phen) 3 ] 3+ and bromomalonic acid.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…20 higher oxidization state catalyst (R8 in FKN mechanism). 21 In varying the sulfuric acid concentration in the iron-catalyzed BZR, we found a strong inverse dependence of period time on acidity. In simulations of the kinetics of the iron-catalyzed reaction, strong agreement with experiment was found by including second-order proton catalysis of the electron transfer reaction (reaction R9 in ref 21, shown below) between [Fe(phen) 3 ] 3+ and bromomalonic acid.…”
Section: Introductionmentioning
confidence: 72%
“…We have found in our previous experimental work that this ferriin reduction is proton-catalyzed. 21 This finding suggested that the VEA values of OSL complexes of ferriin should increase upon OSL protonation. Indeed, this expectation is borne out in the computed data.…”
Section: Ferroin−ferriin Redox Energiesmentioning
confidence: 95%
See 1 more Smart Citation
“…An example of a loop that is illegal because it contains an unnecessary process is provided by a mechanism recently proposed for the reaction of bromate with malonic acid as catalyzed by [Fe­(phen) 3 ] 3+ . This 14-step mechanism includes the following case 2 loop The loop is obtained by combining the steps so that R4b = R4 + A1.…”
Section: Resultsmentioning
confidence: 99%
“…An example of a loop that is illegal because it contains an unnecessary process is provided by a mechanism recently proposed for the reaction of bromate with malonic acid as catalyzed by [Fe(phen) 3 ] 3+ . 45 (R4b)…”
Section: ■ Results and Discussionmentioning
confidence: 99%